Dynamic characteristics analysis of mats of ballasted track on bridge - Xiao Hong; Gao Liang; Wu Kaiwei (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
A complete vehicle-ballasted track-bridge coupling dynamic model is established. A program to analyze dynamic characteristics is also invented, which is the first time to systematically analyze the dynamic characteristics of vehicles, tracks and bridges when using mats under ballast on the rigid foundation of bridge, in China. The results show that:(1) The mats under ballast are able to reduce vibration of the train and the wheel-rail forces by a certain extent, which increase the comforts of passengers.(2) The mats under ballast are able to reduce the stress of ballast, which has a great practical significance on avoiding ballast powdering and reducing maintenance work of ballast. (3) The mats under ballast are able to reduce the vibration of bridges. It has a great significance on avoiding the lateral flow deformation of ballast under dynamic loads, keeping good track geometry to ensure the safety of operation. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1575